Ameilorative effect of lycopine against cisplatin toxicity in rats - Ehgendy, Fatma; Waheed, Rania M.; Ibrahim, Samer; Said, Elshaimaa; Elsayed, Faten (International Journal of Pharmacology and Toxicology, 2021)
The following study aimed to investigate the hepato and neuro protective efficacy of Lycopine against Cisplatin which induced hepatotoxicity and neurotoxicity. Twenty Five male Wister rats were used for this experiment they were equally divided into 5 groups (5 rats per group): group (1) served as control group they were injected 1ml saline orally once daily for 20 day, group (2) served as Corn Oil group and they were administrated 1 mL Corn Oil orally once daily for 20 days, group (3) served as Lycopine group and they were administrated (10 mg/kg b.wt) Lycopine orally once daily for 20 days. , group (4) served as Cisplatin treated group and they were injected (6 mg/kg b.wt.) intrapertonialy once at day 10 of experiment and group (5) Lycopine+Cisplatin group and were administrated 10 mg/kg b.wt Lycopine orally once daily for 20 days and injected 6 mg/kg b.wt.) intraperitonialy once at day 10 . Result revealed that Cisplatin induced liver damage indicated by significant increase in liver biomarkers ALP, AlT, AST along with significant decrease in albumin, Moreover marked increase increase in tissue concentrations of malondialdehyde(MDA) and Total antioxidant(TAC) and reduce tissue Glutathione reductase(GSH),that indicated oxidative stress Also results revealed up regulation IL-6 and down regulation IL-10 in liver and brain tissue in compared to control group . However, interestingly concurrent adminsteration of the Lycopine orally at dose level of 10mg/kg b.wt for 20 days with Cisplatin can mitigate these toxic effects caused by Cisplatin.So it is concluded that the antioxidant and the anti-inflammatory effects of Lycopine moderate the Cisplatin-induced hepato and neurotoxicity.